A Field Survey on Usage of Air-conditioners and Windows in Terraced House Areas in Johor Bahru City - Kubota, Tetsu; Ahmad, Supian (2006)

(untitled)
This paper presents the findings of a questionnaire survey on usage of air-conditioners and windows among selected households in terraced house areas in Johor Bahru City, Malaysia. The results showed 62% of respondents owned an average of 2.3 air-conditioners. It was suggested that the reduction of both numbers and use of air-conditioners would be one of particularly important means for energy-saving among households in terraced house areas. Although approximately 80% of respondents opened their windows during the daytime, only around 10% did so during the nighttime. It is important to encourage occupants to open their windows especially during the nighttime for utilizing the night ventilation.